Роль львівських братсва у розвитку філософсько-правової думки в Україні у кінці XVI – на початку XVI ст. - Колич, Ольга (Видавництво Львівської політехніки, 2013)
Preconditions and causes of brotherhoods in Ukraine, particularly in Lviv have been analyzed in the work. Religious, political, social and economic situation in Ukraine at the end of the XVIth and at the beginning of the XVIIth centuries and its influence on the brotherhoods and on the formation of polemic struggle, which touched philosophical and legal political, religions questions are enlightened. Ideological orientations in the activities of brotherhoods, their part in the development of the educations and culture in Ukraine at the end of the XVIth century – in the beginning of the XVIIth century are investigated. The main philosophicallegal and political views of the figures of brotherhood movement after adopting Union of Brest are examined. Political and cultural significance of brotherhood activities for Ukrainian state both in the period of religious polemic struggle at the end of the XVIth-beginning of the XVIIth centuries, and nowadays is studied.
Keywords: Львівські братства; ідеї братств; полемічна боротьба; ідеологічна боротьба; Берестейська унія; філософсько-правові погляди в Україні у XVI-XVII ст.